2017
DOI: 10.1371/journal.pone.0168254
|View full text |Cite
|
Sign up to set email alerts
|

Lower Urinary Tract Infection and Subsequent Risk of Prostate Cancer: A Nationwide Population-Based Cohort Study

Abstract: PurposeWe investigated whether lower urinary tract infection (LUTI), including cystitis or urethritis, is associated with an increased risk of developing prostate cancer (PCa), in a nationwide population-based cohort study.MethodsWe identified 14,273 men newly diagnosed with LUTI (9347 with cystitis, and 4926 with urethritis) between 1998 and 2011, from the Taiwan Longitudinal Health Insurance Database 2000. Each patient was randomly frequency-matched with 4 men without LUTI, based on age and index year of dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
1
9
1
Order By: Relevance
“…Our null results for lower urinary-tract infections in relation to PCa risk were somewhat unexpected and are inconsistent with the results reported by Fan et al who found a possible etiological role for urethritis and cystitis in the development of PCa [ 5 ]. In particular, they found that urethritis had the most significant increase in PCa risk with an OR of 1.72 (95% CI: 1.26–2.34).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our null results for lower urinary-tract infections in relation to PCa risk were somewhat unexpected and are inconsistent with the results reported by Fan et al who found a possible etiological role for urethritis and cystitis in the development of PCa [ 5 ]. In particular, they found that urethritis had the most significant increase in PCa risk with an OR of 1.72 (95% CI: 1.26–2.34).…”
Section: Discussioncontrasting
confidence: 99%
“…Inflammation of the prostate gland (prostatitis) is also known to be attributed by infection of the microorganisms that are causative of lower urinary tract infections (LUTIs). With a link between the infectious agents, inflammation and the location of the prostate gland, a potential association between lower urinary-tract infections and PCa may be conceived [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, bladder cancer had shown statistically significant association with urinary tract infection in a study done by Richards et al [39]. A study by Fan et al in 2017 had also identified an association between prostate cancer and bacteriuria [40]. Another study by Sun et al in 2013 had also confirmed the association among urinary tract cancers and asymptomatic bacteriuria [8].…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, prostatitis, STIs, and UTIs, which have been reported to increase the risk of PCa, also affect the risk of epididymo-orchitis. [1821] Prostatitis, or chronic inflammation of the prostate, further results in carcinogenesis of the prostate. Wang et al conducted a study of 355 men with gonorrhea and 1420 controls and found that gonorrhea resulted in a 5-fold increased risk of PCa.…”
Section: Discussionmentioning
confidence: 99%